A complete proteomic profile of human and bovine milk exosomes by liquid chromatography mass spectrometry. (3rd August 2021) - Vaswani, Kanchan Manohar; Peiris, Hassendrini; Qin Koh, Yong; Hill, Rebecca J.; Harb, Tracy; Arachchige, Buddhika J.; Logan, Jayden; Reed, Sarah; Davies, Peter S. W.; Mitchell, Murray D.
ABSTRACT: Background: The present study investigates the proteomic content of milk-derived exosomes. A detailed description of the content of milk exosomes is essential to improve our understanding of the various components of milk and their role in nutrition. Methods: The exosomes used in this study were isolated as previously described and characterized by their morphology, particle concentration, and the presence of exosomal markers. Human and bovine milk exosomes were evaluated using Information-Dependent Acquisition (IDA) Mass Spectrometry. A direct comparison is made between their proteomic profiles. Results: IDA analyses revealed similarities and differences in protein content. About 229 and 239 proteins were identified in the human and bovine milk exosome proteome, respectively, of which 176 and 186 were unique to each species. Fifty-three proteins were common in both groups. These included proteins associated with specific biological processes and molecular functions. Most notably, the 4 abundant milk proteins lactadherin, butyrophilin, perilipin-2, and xanthine dehydrogenase/oxidase were present in the top 20 list for both human and bovine milk exosomes. Conclusion: The milk exosome protein profiles we have provided are crucial new information for the field of infant nutrition. They provide new insight into the components of milk from both humans and bovines.